2020
DOI: 10.1097/bsd.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Preoperative Duration of Symptoms With Clinical Outcomes and Minimal Clinically Important Difference Following Anterior Cervical Discectomy and Fusion

Abstract: Study Design: This was a retrospective cohort study. Objective: The purpose of this study is to examine whether the time duration from symptom onset to operative treatment is associated with postoperative clinical improvement after anterior cervical discectomy and fusion (ACDF). Summary of Background Data: There is a paucity of literature regarding the influence of preoperative symptom duration on patient-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Interestingly, however, Jenkins et al reported that patients with higher preoperative PHQ-9 scores actually achieved MCID in NDI at higher rates than those with lower preoperative depression scores. Considering the close relationship that has been demonstrated between disability and both mental health and duration of symptoms, 5,20 we surmised that duration of symptoms would be an important factor for postoperative mental health outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Interestingly, however, Jenkins et al reported that patients with higher preoperative PHQ-9 scores actually achieved MCID in NDI at higher rates than those with lower preoperative depression scores. Considering the close relationship that has been demonstrated between disability and both mental health and duration of symptoms, 5,20 we surmised that duration of symptoms would be an important factor for postoperative mental health outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in cervical spine patients have demonstrated notable associations between preoperative symptom severity and depressive symptoms. Jenkins et al 5 reported markedly poorer pain, disability, and physical function scores among patients with PHQ-9 scores of 5 or greater. In particular, diminished physical function or ambulatory ability has been tied to diminished mental health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations